The Effect of School Leadership and Work Motivation on Teacher Performance at SMP PGRI 1 Palembang - Rachmawati; Fitria, Happy; Puspita, Yenny (Jurnal Pendidikan Tambusai, 2021)
The purpose of this study was to analyze the influence of principal leadership, work motivation on teacher performance at SMP PGRI 1 Palembang. This type of research is quantitative research, with quantitative descriptive methods. Data collection techniques used were observation, documents, interviews, and questionnaires. The results showed: 1) There is a significant influence between principal leadership on teacher performance at SMP PGRI 1 Palembang, 2) There is a significant influence between principal motivation on teacher performance at SMP PGRI 1 Palembang, 3) There is a climate of leadership and motivation. the performance of the principal teachers at SMP PGRI 1 Palembang.